An efficient five-axis machining method of centrifugal impeller based on regional milling. Issue 1 (October 2016) - Fan, Hong-Zhou; Xi, Guang; Wang, Wei; Cao, Yan-Long
Abstract This paper presents an efficient five-axis machining method of centrifugal impeller based on regional milling. As the base of the machining method, geometry of the centrifugal impeller and blade surface is analyzed, and sub-machining regions are presented through the division of the double three-cubic d non-uniform rational B-spline (NURBS) surface. In rough milling, the cutter parameters, tool path interval, tool path curves, and the fixed tool axis vector are calculated by the novel algorithm based on regional milling; the biggest cutter and smaller tool path length are obtained. In finish milling, for the aerodynamic performance of the finished impeller, the tool path curves are modified and interlinked to make them uniform and orderly. A modified algorithm of the finish milling of the blade surface is proposed, and not only are the machining errors reduced; their reasonable distribution is also realized. Numerical simulation and a real test impeller are presented as the test of the proposed method.